Die-off Rates of Escherichia coli in a Silt Loam Soil - Ling, T. Y.; Jong, H. J.; Kasing, A.; Wan Sulaiman, W. H. (Universiti Malaysia Sarawak, 2009)
Even though animal waste is a resource, fecal contamination of soil is concern for the public. Therefore, in study, die-off of Escherichia coli (E.coli) was investigated in a silt loam soil under different temperature and pH. Results indicated that E. coli persisted about a month under 30°C and and pH4 and lowest under 20°C and pH6. It is recommended that animal waste be applied during hot season of the year before liming of soil is carried out.